2016
DOI: 10.14257/ijgdc.2016.9.8.12
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Modeling and Assessment of Electric Vehicle Motor Using Fault Tree and Fuzzy Petri Nets

Abstract: Performing reliability analysis of electric vehicle motor has an important impact on its safety. To do so, this paper proposes its reliability modeling and evaluation issues of electric vehicle motor by using fault tree (FT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…To show the applicability and flexibility of the proposed RPNs for knowledge representation and acquisition, a case study of assessing the reliability of an electric motor system (Wang et al, 2016) is presented in this section.…”
Section: Illustrative Examplementioning
confidence: 99%
See 1 more Smart Citation
“…To show the applicability and flexibility of the proposed RPNs for knowledge representation and acquisition, a case study of assessing the reliability of an electric motor system (Wang et al, 2016) is presented in this section.…”
Section: Illustrative Examplementioning
confidence: 99%
“…To demonstrate the rationality and advantages of the proposed RPN model, it is compared with the extended FPNs (EFPNs) (Wang et al, 2016), the cloud reasoning Petri nets (CRPNs; Liu et al, 2018), the FPR method (Yeung & Ysang, 1998), and the dynamic uncertain causality graph (UCG; Li et al, 2020). The reasoning results of the terminating place obtained by these methods are listed in Table 7.…”
Section: Illustrative Examplementioning
confidence: 99%
“…Based on the data listed in Table 11, the failure rate of motor controller parts is calculated by substituting these parameters into (8)(9)(10)(11)(12). The calculation results are listed in Table 12.…”
Section: B Evaluation Of Failure Rates Of Motor Controller Partsmentioning
confidence: 99%
“…The reliability of drive motor and electronic converter for power supply was also studied by scholars. For example, the reliability of the drive motor of EVs was studied in [9], [10] by using a combined fault tree and Petri net approach, and the fault logical causes by the winding insulation and bearing with higher fault rate were investigated in [11] by the approach of fault tree analysis. The reliability of bidirectional DC/DC converters of EVs was studied in [12]; the age and life of power converter components were estimated in [13] based on a survey, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In order to accurately assess the reliability of lithium-ion batteries, a reliability model considering the dependency among cells for the overall degradation of lithium-ion battery packs was built in [12]. Apart from these, the reliability of the stator and rotor components in permanent magnet synchronous motors for BEVs has been studied using a combined fault tree and Petri net approach [13,14]. The fault logic of failures caused by key components of the drive motor (i.e., stator and rotor windings and bearings) has also been investigated [15][16][17] using the approach of fault tree analysis (FTA); the results showed that different components have different effects on the reliability of the entire drive motor and also suggested that reliability issues in the drive motor and motor controller should be investigated together when assessing the reliability of the motor system; otherwise, an unreliable reliability prediction may be obtained.…”
Section: Introductionmentioning
confidence: 99%